2022
DOI: 10.1039/d1cp04014f
|View full text |Cite
|
Sign up to set email alerts
|

The excited-state dynamics of the radical anions of cyanoanthracenes

Abstract: The radical anion of 9,10-dicyanoanthracene (DCA) has been suggested to be a promising chromophore for photoredox chemistry, due to its nanosecond excited-state lifetime determined from indirect measurements. Here, we investigate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 82 publications
(107 reference statements)
3
50
0
Order By: Relevance
“…While earlier studies reported a lifetime in the range of several nanoseconds for 2* DCA •– , 138 , 139 this was questioned later, and in particular the luminescence of 2* DCA •– was doubted. Lifetimes on the picosecond timescale seem more realistic for 2* DCA •– , 101 , 140 142 in line with the excited-state lifetimes reported for other radical anions. 97 , 102 , 143 145 Furthermore, concerning the reactivity and stability of DCA •– , a variety of very different observations were reported in the literature, including claims of reasonably good stability of DCA •– , 146 as well as observations of comparatively rapid degradation reactions with the solvent, reaction intermediates or oxygen.…”
Section: Mechanistic Investigationssupporting
confidence: 84%
See 2 more Smart Citations
“…While earlier studies reported a lifetime in the range of several nanoseconds for 2* DCA •– , 138 , 139 this was questioned later, and in particular the luminescence of 2* DCA •– was doubted. Lifetimes on the picosecond timescale seem more realistic for 2* DCA •– , 101 , 140 142 in line with the excited-state lifetimes reported for other radical anions. 97 , 102 , 143 145 Furthermore, concerning the reactivity and stability of DCA •– , a variety of very different observations were reported in the literature, including claims of reasonably good stability of DCA •– , 146 as well as observations of comparatively rapid degradation reactions with the solvent, reaction intermediates or oxygen.…”
Section: Mechanistic Investigationssupporting
confidence: 84%
“…Gray circles mark the elementary reaction steps of (I) TTET, (II) reductive quenching of 3* DCA by DiPEA, and (III) substrate activation after excitation of DCA •– . The doublet excited state of that radical anion is extremely short-lived, 101 and therefore, 2* DCA •– is set in quotation marks, to emphasize the possibility that the photoreaction could in fact predominantly occur from preaggregated DCA •– /substrate encounter complexes, or could even involve some DCA photodegradation products.…”
Section: Mechanistic Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a conceptual level, the approach of our study is illustrated by Figure 5. As noted in the introduction, radical monoanions of perylene diimides and related compounds can be generated photochemically or electrochemically by single electron transfer (SET), leading to highly reducing species with very short excited‐state lifetimes (Figure 5 a, left) [5–7, 22, 43, 46] . Alternatively, closed‐shell monoanions with longer‐lived excited states that are also very reducing have been produced by deprotonation of suitable pre‐catalysts with bases (Figure 5 a, right) [16b] .…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the introduction, radical monoanions of perylene diimides and related compounds can be generated photochemically or electrochemically by single electron transfer (SET), leading to highly reducing species with very short excited‐state lifetimes (Figure 5 a , left). [ 5 , 6 , 7 , 22 , 43 , 46 ] Alternatively, closed‐shell monoanions with longer‐lived excited states that are also very reducing have been produced by deprotonation of suitable pre‐catalysts with bases (Figure 5 a , right). [16b] Our work adds the concept of two‐electron transfer (“2‐ET” in Figure 5 b ) to convert a pre‐catalyst into a closed‐shell dianion with high reducing power and comparatively long excited‐state lifetime.…”
Section: Discussionmentioning
confidence: 99%